LoRA Gateway Coverage and Capacity Analysis for Supporting Monitoring Passive Infrastructure Fiber Optic in Urban Area - Enriko, I Ketut Agung; Gustiyana, Fikri Nizar; Giri, Gede Chandrayana (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2023)
In the era of digital transformation, telecommunications infrastructure has become the backbone of global connectivity. Optical Distribution Cabinet (ODC) is a crucial part of an optical network that distributes signals to various points in the network. Maintenance and monitoring of ODCs have become essential to ensure optimal availability and performance. However, conventional approaches are often expensive and difficult to implement. The objective of this study is to develop a LoRaWAN network with the purpose of determining the required number of gateways. Additionally, the research aims to devise an IoT-basedODC device monitoring system within the FTTH network, utilizing data from PT. Telkom Witel Bandung. The approach involves employing simulation techniques through the Atoll apps v 3.40. Multiple calculation stages are applied to expect RSSI and SINR parameters within an area spanning 188.96 km². The study employs a frequency of 920 MHz, a bandwidth of 125 kHz, and a spreading factor of 10. The data analysis includes RSSI and SINR signals. As a result of calculations and planning simulations, this study recommended the use of nine gateways and achieved an RSSI parameter of -70. 35 dBm and a SINR parameter of 17. 33 dBm.